The Limitation of Unproductive Binding of Cellulases to Lignin by Ozone Pretreatment - Congfei Zhang; Lihong Zhao; Weiying Li; Junli Ren; Hongyuan Wang; Beihai He (Applied Sciences, 2024)
The limitation of enzymatic saccharification of lignocellulose is attributed to the nonproductive adsorption between lignin and cellulase. This study aims to investigate the effects of ozone pretreatment on the physical structure and chemical properties of milled wood lignin (MWL). The objective is to reduce the non-productive adsorption of cellulase on lignin. The structure–activity relationship between the physical structure of MWL and the occurrence of nonproductive adsorption was analysed using two-dimensional heteronuclear single quantum coherence–nuclear magnetic resonance (HSQC-NMR) and phosphorus-31 nuclear magnetic resonance spectrum (31P-NMR), etc. The results indicate that ozone pretreatment resulted in a decrease in the phenolic hydroxyl content and S/G ratio, an increase in the carboxyl content, and a negative zeta potential of MWL. The maximum adsorption capacity decreased from 25.77 mg/g to 10.09 mg/g, the Langmuir constant decreased from 13.86 mL/mg to 10.11 mL/mg, and the binding strength decreased from 357.14 mL/g to 102.04 mL/g, as determined by Langmuir isothermal adsorption. This suggests that ozone pretreatment resulted in a reduction in the hydrophobicity of lignin and a weakening of the electrostatic attraction between lignin and cellulase, thereby effectively reducing the non-productive adsorption of cellulase on lignin. This study provides an environmentally friendly pretreatment technique and comprehensively analyses the structural changes of ozone-treated MWL. These findings contribute to a deeper understanding of the interaction between lignin and cellulase.